National Standards of Education affect the employment opportunities of vocational high school graduates - Eka Hendi Andriansyah; Putri Ulfa Kamalia (Jurnal Pendidikan Vokasi, 2021)
This study aims to find out the National Standard of Education indicators that are the most dominant in influencing vocational schools, especially in producing the expected outcomes. The research is aimed at vocational schools in the field of economics and finance in the city of Surabaya. The data collection includes NSE assessment data from BAN-SM and employment opportunities from 22 schools. The object of further research is processed with the WARP PLS program. The study results found that there is a variable signification between the National Standard of Education on Employment Opportunities of Vocational School Graduates. Positive influence indicates that the higher/better the National Standard of Education, the higher/improved the outcome of Vocational School Graduates. Based on the results of the analysis indicator, the study found the NSE 8 indicator is the Education Assessment Standard which has the highest component weight value that indicates that the NSE's institutions are most important in producing graduates who are absorbed in the workforce. Then, the second-highest order is the NSE's indicative 2 and 1, namely process and content standards. The indicator with the lowest value is the indicative standard educators and educational personnel and facilities and infrastructure standard.